Impact of glacier changes and permafrost distribution on debris flows in Badswat and Shishkat catchments, Northern Pakistan - Hassan, Wajid; Su, Feng-huan; Liu, Wei-ming; Hassan, Javed; Hassan, Muzammil; Bazai, Nazir Ahmed; Wang, Hao; Yang, Ze-wen; Ali, Muzaffar; Castellanos, Daniel Garcia (Journal of Mountain Science, 2023)
Knowledge of glacier changes and associated hazards is of great importance for the safety consideration of the population and infrastructure in the mountainous regions of Upper Indus Basin (UIB). In this study, we assessed the variations in glacier velocity, glacier surface elevation change, meteorological conditions, and permafrost distribution in Badswat and Shishkat catchments located in UIB to access the potential impact on the occurrence of debris flow in both catchments. We find that the glacier surface velocity increased during the debris flow event in the Badswat catchment and the mean daily temperature was 3.7 degrees C to 3.9 degrees C higher in most of the locations. The enhanced glacier surface elevation lowering period coincide with the rise in temperature during spring and autumn months between 2015 to 2019 in Badswat catchment. The source region of debris flow falls within the lower boundary of permafrost occurrence zone and lies below the 0 degrees C isotherm during late spring and summer months. In Shishkat catchment the 0 degrees C isotherm reaches above the debris flow source area during August and the glacier do not show any significant variations in velocity and surface elevation change. The debris flow source area is adjacent to the slow-moving rock glacier in Shishkat catchment while in Badswat catchment the debris flow initiated from the former glacier moraine. Both catchments are largely glacierized and thus sensitive to changes in climatic conditions and changes in the cryosphere response possess significant threats to the population downstream. Continuous monitoring of cryosphere-climate change in the region can contribute toward the improvement of disaster risk reduction and mitigation policies.